Insights from a field day: Biofortified rice innovation for resilient agri-food systems - Vargas Gonzalez, Sandra; Gallego, Sonia; Rendon, Natali (2025)
In September 2025, a Field Day was held in Zapatero, Cartagena (Bolívar, Colombia) as part of the Scaling for Impact program to showcase the progress, benefits, and future prospects of the biofortified rice variety Fedearroz BIOZn035. The event aimed to strengthen resilient agri-food systems, improve food security, and enhance nutrition in rural communities facing climate variability and production challenges.